Study of a sulfide soil deposit at a road construction in Sunderbyn, near Luleå in the north of Sweden - Pousette, Kerstin; Knutsson, Sven (Luleå tekniska universitet, Geoteknologi, 2012)
Godkänd; 2012; 20130117 (pou)